Efficacy of a novel bacteriocin isolated from Lysinibacillus sp. against Bacillus pumilus. (March 2019) - Ahmad, Varish; Ahmad, Khurshid; Baig, Mohammad Hassan; AL-Shwaiman, Hind A.; Al Khulaifi, Manal M.; Elgorban, Abdallah M.; Khan, Mohd Sajid
Abstract: A strain of Lysinibacillus, isolated from spoiled fruits and vegetable wastes, was found having an inhibitory effect against foodborne pathogens. Subjected to study of different physico-chemical parameters followed by characterization based on the 16S rRNA gene, it was found exhibiting resemblance to L. boronitolerans (99%), L. xylanilyticus (98%) and L. macroides (97%) respectively. The isolate was annotated as Lysinibacillus JX402121 and found that the production capacity of the specific product recognized as bacteriocin during growth in medium the bacteriocin was further purified to homogeneity by ammonium sulphate precipitation followed by gel filtration chromatography. MALDI-TOF/MS analysis of the substance revealed it to be a 51 kDa bacteriocin, showing greater resemblance with a catalytic bacterial protein, uracil-5-methyl transferase. Based on the physico-chemical characteristics and N-terminal (IKKAPVQKNENYEV) sequence, this novel bacteriocin was found representing a class III bacteriocin. This was found highly active against foodborne bacterial pathogens, Bacillus pumilus (MIC-22 μg/mL), which is responsible for pumilacidins like food toxin. Having great potential against foodborne pathogens, Lysinibacillus JX402121 isolate will be utilized in the production of bacteriocin that acts as a bio-preservative agent against different food-borne pathogens. Highlights: A strain of Lysinibacillus, isolated from spoiled fruits and vegetable wastes. The isolate was annotated as Lysinibacillus JX402121. Bacteriocin was purified and characterized from this strain by multiple techniques. It represents, class III Bacteriocin and effective against food borne pathogens.